Evaluation of the Dhuha Prayer Program Based on the CIPP Model: Study of Islamic Education in Elementary Schools - Asnur, Herawaty; Muhaemin, Muhaemin; Iman RN, Bustanul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The Duha prayer in schools is a tangible kind of character education that shapes kids' personalities and morals. These ideals must be instilled early in education, especially in elementary school. Therefore, this study aims to evaluate the implementation of the Duha prayer program at Public Elementary School, using the CIPP (Context, Input, Process, Product) model. This study was conducted at Public Elementary School Baebunta District, North Luwu Regency. This qualitative study is descriptive-evaluative, with data obtained through interviews, observations, and documentation involving the principal, teachers, students, and parents. The results of the study indicate that (1) context: the Duha prayer program strengthens the religious character of students and is supported by school policies and the surrounding environment; (2) input: facilities and infrastructure are still limited, such as the lack of a special prayer room, but Islamic religious education teacher resources are adequate; (3) process: implementation is carried out routinely through the habit of two rakaat, joint prayer, and direct guidance by teachers; and (4) product: activities contribute positively to student discipline and habituation of worship, although parental involvement at home still needs to be improved. The conclusion of this study is that the implementation of the Duha prayer at Public Elementary School Baebunta District is going well, despite limited facilities and environmental support that still need improvement. Recommendations are directed at improving prayer facilities, coordinating with parents, and developing more varied strategies for habituating prayer.